SECONDARY OSTEOPOROSIS IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY PATHOLOGY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Osteoporosis (OP) is a progressive multifactorial systemic disease of the skeleton, characterized by a decrease in bone mass and a violation of the structure (microarchitectonics) of bone tissue. Among the diseases that contribute to the development of osteoporosis, a special place is given to chronic obstructive pulmonary diseases: chronic obstructive pulmonary disease (COPD) and bronchial asthma (AD).